An overview on web cookies and privacy - Pirilä, Lauri (2023)
This thesis researches web cookies and their use on the internet. This paper has been carried out as a literature review. The aim is to find out what cookies are, how they are used, what they are used for, how regulations affect cookies, and how are websites’ compliant with the regulations. The aim of this paper is also to provide the reader with useful information about the properties of cookies, their utilization on the server side, and their safety on behalf of information security and privacy. The results of this paper show what cookies are, what threats are associated with the use of web cookies, and how official regulations or laws affect the use and handling of cookies.